2020
DOI: 10.1016/j.stem.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Physiological Basis for Lung Repair and Regeneration: Past, Present, and Future

Abstract: The respiratory system, which includes the trachea, airways, and distal alveoli, is a complex multi-cellular organ that intimately links with the cardiovascular system to accomplish gas exchange. In this review and as members of the NIH/NHLBI-supported Progenitor Cell Translational Consortium, we discuss key aspects of lung repair and regeneration. We focus on the cellular compositions within functional niches, cell-cell signaling in homeostatic health, the responses to injury, and new methods to study lung re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
299
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(308 citation statements)
references
References 229 publications
(270 reference statements)
6
299
0
3
Order By: Relevance
“…Single cell RNA sequencing studies have shown that increased transcriptional noise and upregulation of a core group of age-associated molecular mechanisms -including protein processing-and inflammation-associated genes -are correlated with ageing across mouse cell and tissue types, but additional processes are unique to particular cell types within specific organs, including the lungs (Angelidis et al, 2019;Kimmel et al, 2019). However, to date such studies have not profiled the trachea, which has distinct composition and stem cell biology to the more distal airways (Basil et al, 2020), in detail. During murine tracheal ageing, epithelial cell density is reduced and the proportion of basal cells within the epithelium is slightly decreased, but there is no obvious decline in their in vitro clonogenic potential or differentiation capacity (Wansleeben et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Single cell RNA sequencing studies have shown that increased transcriptional noise and upregulation of a core group of age-associated molecular mechanisms -including protein processing-and inflammation-associated genes -are correlated with ageing across mouse cell and tissue types, but additional processes are unique to particular cell types within specific organs, including the lungs (Angelidis et al, 2019;Kimmel et al, 2019). However, to date such studies have not profiled the trachea, which has distinct composition and stem cell biology to the more distal airways (Basil et al, 2020), in detail. During murine tracheal ageing, epithelial cell density is reduced and the proportion of basal cells within the epithelium is slightly decreased, but there is no obvious decline in their in vitro clonogenic potential or differentiation capacity (Wansleeben et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The lung mesenchyme remains poorly defined without any one marker that demarcates a population with unique features. Advances in nextgeneration sequencing and analysis may add novel dimensions and complexity to how we understand lung mesenchymal subtypes and how they differentially contribute to lung fibrosis and repair [51].…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory system in humans is co-developed with the cardiovascular system via crosstalk and integration of multiple cellular populations (Morrisey and Hogan, 2010). Adult human lungs have functional gas exchange surfaces of about 70 m 2 with a tremendous compensation ability (Basil et al, 2020). Under conditions of repairing cellular loss or lung function deficiency, the alveolar cells are able to self-renew and proliferate to restore normal alveolar structure and gas exchange function, which are regulated via an integrated network of mesenchymal, endothelial, and epithelial cells and other components (Barkauskas et al, 2013;Lee et al, 2017).…”
Section: Improving Alveolar Gas Exchange By Hdr-induced Vasculature Mmentioning
confidence: 99%
“…In addition, the lung microvasculature is shown to contain heterogenic endothelial subpopulations with various vasculogenic capacities coordinately contributing to lung injury response (Niethamer et al, 2020;Stevens et al, 2008). Notably, proliferation of the lung endothelial cell subpopulation is enhanced during influenza-mediated lung injury (Basil et al, 2020;Niethamer et al, 2020). On the other hand, cutaneous low-dose radiation has been shown to increase tissue vascularity through upregulation of angiogenic and vasculogenic pathways (Thanik et al, 2010).…”
Section: Improving Alveolar Gas Exchange By Hdr-induced Vasculature Mmentioning
confidence: 99%